THE COLD IN THE CONSERVATION OF FOOD AND COLD STORES IN THE REGION OF ATHENS AND PIRAEUS - ΑΝΑΣΤΑΣΙΟΥ, Α. Χ. (Journal of the Hellenic Veterinary Medical Society, 1972)
The author after a brief survey of the history of frigorifie industry, the different techniques and procedures for preserving perishable foodstreffs, the recent development in lyophilization, the procedures for conditioning in nitrogen atmosphere etc.,he refers to the cold stores of Athens and Piraeus. In Greece the cold stores are implanted a) in the regions where fruit and vegetable production is dominant (Northern Greece), to cool the products of vegetable origin in order to send and export them in good condition and b) in the region of Athens and Piraeus which constitutes the zone of the biggest consommation in Greece and where the importation traffic of frozen animal origin products is very important. The total volume of cold stores in Greece is 1.127.000 m3 of which 407.000 m3 in Athens and Piraeus (63 % utilizable for —15° to —20° C). The number of cold stores in this region is 29 of which 10 are polyvalent. The author makes also some remarks on these cold stores which despite the evolution in this field they are still in the region of Athens and Piraeus of cubic form, with many floors and of a solid construction with concrete. The volume of the chambers is 300 to 2.300 m3, the height is of 3 - 6 meters, the ammonia is predominant and the insulation is being made with cork and polysterene. Finally, the author makes some suggestions concerning the advantages of one floor construction and of using special apparatus for the palettization which is almost inexistant to day in this region.